Contractual Validity and Notary Liability in Fraus Legis Nominee Agreements: Keabsahan Kontraktual dan Tanggung Jawab Notaris dalam Perjanjian Nominee Fraus Legis - Bunayya Damaria Zamie; Abdul Rokhim; Mutiara Balqis Nabielah Rahmi (Academia Open, 2026)
General Background Globalization and foreign investment liberalization precipitate complex legal mechanisms separating formal and beneficial ownership across diverse jurisdictions. Specific Background Within Indonesia, these arrangements frequently bypass statutory restrictions governing land rights and corporate asset control. Knowledge Gap Although previous scholarship addresses these contracts sectorally, a comprehensive framework integrating the fraus legis doctrine, beneficial ownership concepts, and professional obligations remains critically absent. Aims This normative study analyzes contractual validity parameters for these mechanisms and evaluates the corresponding legal responsibilities of public officials drafting related authentic deeds. Results The doctrinal analysis reveals that while these unnamed contracts theoretically align with freedom of contract principles, they become null and void when utilized to evade mandatory laws, thereby lacking a lawful cause. Furthermore, officials functioning as guardians of substantive legality face civil, administrative, and criminal liabilities if they passively facilitate unlawful asset concealment. Novelty This research distinctly synthesizes civil contract principles with professional liability frameworks, establishing a unified approach to combat systemic statutory circumvention. Implications Consequently, legislative revisions must mandate rigorous beneficial owner identification and authorize practitioners to reject legally deficient transactions, thereby safeguarding national legal certainty. Highlights Unnamed contracts designed to circumvent mandatory statutory restrictions lack lawful causation and are consequently nullified. Public officials must act as guardians of substantive legality rather than passive recorders of party intentions. Legislative revisions requiring rigorous beneficial owner identification will significantly prevent authentic deed misuse in corporate transactions. Keywords Beneficial Ownership; Substantive Legality; Unnamed Contracts; Authentic Deeds; Legal Circumvention